Makerere University College of Health Sciences' role in addressing challenges in health service provision at Mulago National Referral Hospital - Sekandi Juliet; Nshimye Edith; Kasangaki Arabat; Mbabali Speciosa; Tweheyo Raymond; Tugumisirize Joshua; Kizza Irene B; Groves Sara; Kennedy Caitlin E (BMC, 2011)
Abstract Background Mulago National Referral Hospital (MNRH), Uganda's primary tertiary and teaching hospital, and Makerere University College of Health Sciences (MakCHS) have a close collaborative relationship. MakCHS students complete clinical rotations at MNRH, and MakCHS faculty partner with Mulago staff in clinical care and research. In 2009, as part of a strategic planning process, MakCHS undertook a qualitative study to examine care and service provision at MNRH, identify challenges, gaps, and solutions, and explore how MakCHS could contribute to improving care and service delivery at MNRH. Methods Key informant interviews (n=23) and focus group discussions (n=7) were conducted with nurses, doctors, administrators, clinical officers and other key stakeholders. Interviews and focus groups were tape recorded and transcribed verbatim, and findings were analyzed through collaborative thematic analysis. Results Challenges to care and service delivery at MNRH included resource constraints (staff, space, equipment, and supplies), staff inadequacies (knowledge, motivation, and professionalism), overcrowding, a poorly functioning referral system, limited quality assurance, and a cumbersome procurement system. There were also insufficiencies in the teaching of professionalism and communication skills to students, and patient care challenges that included lack of access to specialized services, risk of infections, and inappropriate medications. Suggestions for how MakCHS could contribute to addressing these challenges included strengthening referral systems and peripheral health center capacity, and establishing quality assurance mechanisms. The College could also strengthen the teaching of professionalism, communication and leadership skills to students, and monitor student training and develop courses that contribute to continuous professional development. Additionally, the College could provide in-service education for providers on professionalism, communication skills, strategies that promote evidence-based practice and managerial leadership skills. Conclusions Although there are numerous barriers to delivery of quality health services at MNRH, many barriers could be addressed by strengthening the relationship between the Hospital and MakCHS. Strategic partnerships and creative use of existing resources, both human and financial, could improve the quality of care and service delivery at MNRH. Improving services and providing more skills training could better prepare MakCHS graduates for leadership roles in other health care facilities, ultimately improving health outcomes throughout Uganda.